2018
DOI: 10.1016/j.eurpsy.2017.12.027
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of etiological knowledge and mental illness stigma on healthcare utilisation in the community: A structural equation model

Abstract: Our results indicate that campaigns promoting early healthcare utilisation should focus on different strategies to promote facilitation and reduce barriers to mental healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 66 publications
6
42
0
1
Order By: Relevance
“…Interestingly, treatment satisfaction did not seem to influence current help-seeking. Considering the reported significant role of attitudes towards help-seeking [5759], the insignificant role of treatment satisfaction that might shape current attitudes towards help-seeking was surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, treatment satisfaction did not seem to influence current help-seeking. Considering the reported significant role of attitudes towards help-seeking [5759], the insignificant role of treatment satisfaction that might shape current attitudes towards help-seeking was surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although the knowledge of MI has been improved (Kendler and Prescott, 2006; Schnyder et al, 2018), scientific literature showed that people usually perceive individuals with MI as dangerous (Angermeyer and Matschinger, 2005). Walker and Read (2002) showed that people's dominant impression on MI is that it leads to unpredictable behaviors and loss of control.…”
mentioning
confidence: 99%
“…This may be due to a general lack of knowledge concerning mental health services (Hundt et al, 2018;Saechao et al, 2012), which is often impacted by poor access to mental health resources (Browne et al, 2019;Hundt et al, 2018;Pfeiffer et al, 2016). Acquiring accurate knowledge about the types and purposes of different available mental health services is commonly cited as a precursor to access (Schnyder et al, 2018;Wei, Carr, Alaffe, & Kutcher, 2019). Yet, even when individuals are aware of mental health services, research shows that a lack of confidence in mental health providers can be another barrier to accessing help (Gaston, Earl, Nisanci, & Glomb, 2016;Rughani, Deane, & Wilson, 2011).…”
Section: Barriers To Accessing Mental Health Servicesmentioning
confidence: 99%
“…Researchers were interested in how engagement with the storefront might impact mental health stigma. Following research findings cited in the literature review, some studies (Schnyder et al, 2018;Wei, Carr, Alaffe, & Kutcher, 2019) show how increased mental health knowledge can reduce stigmatizing attitudes toward help-seeking behaviour among a variety of social groups. A similar effect may be measured by testing whether or not the number of visits to the social enterprise storefront contributes to more positive perceptions of mental health service use.…”
Section: Case Examplementioning
confidence: 99%